An Application of Student Self- Assessment and Newman Error Analysis in Solving Math Problems - Louida P. Patac (Recoletos Multidisciplinary Research Journal, 2015)
The mathematics educators are looking for innovations that remediate the errors committed by the students in solving math problems. In seeking for solutions, we apply the Student Self –Assessment (SSA) method and Newman Error Analysis (NEA) method to circumvent these errors. The SSA is a strong formative educational tool that enhances selfconfidence to become more independent in assessing their work. While, NEA serves as a powerful classroom diagnostic assessment to identify the skills of the students. It enables the teacher to devise and apply more appropriate teaching strategies and procedures that ignite the students’ interest towards the subject. Out of the 179-students participating in the action research project, we discover that most of the error patterns are due to lack of understanding and transformation skills in solving word problems. With this result, the students encounter language difficulty and immature computational skills. To this end, the investigation and remediation of common math errors was a success in improving and achieving the learning goals and promotes positive behavioral changes towards the subject. The realization of these outcomes is through the inclusion of SSA and NEA. To sustain the learning goals of the students, it should be properly facilitated to come up with a fruitful learning process.